1998
DOI: 10.1159/000030036
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological Subtypes and Prognosis of Gastric Cancer Are Correlated with the Expression of Mucin-Associated Sialylated Antigens: Sialosyl-Lewis<sup>a</sup>, Sialosyl-Lewis<sup>x</sup> and Sialosyl-Tn

Abstract: The expression of three sialylated mucin-associated antigens – sialosyl-Lewisa (SLEA), sialosyl-Lewisx (SLEX) and sialosyl-Tn (STN) – and their correlation with the TNM stage, histopathological growth pattern and prognosis was investigated in a series of 127 gastric carcinomas. Various classification systems (pTNM, WHO and Laurén) did not display any correlation with an expression of the sialomucin antigens under study. SLEA reactivity was strongly associated with an unfavorable outcome o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 27 publications
0
35
0
Order By: Relevance
“…A streptavidin-biotin-peroxidase method was applied as described previously [11, 22, 26]. Briefly, after routine processing of 5-µm-thick tissue specimens and blocking of endogenous peroxidase (1% H 2 O 2 ) as well as unspecific protein binding sites (normal swine serum X901, DAKO, Copenhagen, Denmark), the sections were incubated with primary MAbs for 30 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A streptavidin-biotin-peroxidase method was applied as described previously [11, 22, 26]. Briefly, after routine processing of 5-µm-thick tissue specimens and blocking of endogenous peroxidase (1% H 2 O 2 ) as well as unspecific protein binding sites (normal swine serum X901, DAKO, Copenhagen, Denmark), the sections were incubated with primary MAbs for 30 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…In some studies, this antigen revealed a predictive value indicating a worsening of prognosis [5, 6, 7, 8, 9], either independent of pTNM stage or in defined stages. Others observed such an effect only in subpopulations according to Laurén or Borrmann [10, 11]. In another study, a prognostic value of sialosyl-Tn was not detected [12].…”
Section: Introductionmentioning
confidence: 98%
“…2). SLe a and SLe x have been demonstrated to be highly expressed in many malignant cancers, and SLe x expression levels have been correlated with poor survival in cancer patients 44,45 . SLe x is the well-known ligand for selectins 46 , which are vascular cell adhesion molecules that belong to a family of C-type lectins (which require calcium for binding).…”
Section: Sialylationmentioning
confidence: 99%
“…2,71,186 Typically, the blood group antigens sialyl-Lewis x and sialyl-Lewis a exhibit a tumor-associated expression that may correlate with disease progression and a worse prognosis, at least in certain subgroups of cancer patients. 2,187,188 Their presence on MUC1 glycoforms derived from pancreatic and colonic carcinoma cell lines was described. 189 Interactions of these oligosaccharides with selectins, physiologically involved in the leukocyte recruitment and extravasation during inflammatory processes, 190 may be relevant events in metastasis.…”
Section: Muc1 Expressed On Neoplastic Cells Exhibits Altered O-glymentioning
confidence: 99%